(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
This article describes our inter-professional mental health service for adults with intellectual disability and/or autism spectrum disorder. The service consists of an inpatient unit and outpatient program that are closely aligned and operate within a mental health and addictions teaching hospital. We provide information about recent changes to our model of care and the structures and activities that are used to support inter-professional team development and team functioning. Roles and functions of different mental health professionals on the team are outlined and case examples of adults with intellectual disability and complex mental health needs are provided to illustrate how the inter-professional team members work together.